Green synthesis, characterization and anticancer activity of luminescent gold nanoparticles capped with apo-α-lactalbumin. Issue 41 (7th May 2015) - Yarramala, Deepthi S.; Doshi, Sejal; Rao, Chebrolu P.
<x xml:space="preserve">Abstract</x> A green synthesis was developed to prepare protein coated gold nanoparticles (NPs) where apo-α-lactalbumin was used as reducing and stabilizing agent. The NPs are luminescent and non-toxic to normal cells but more toxic to MCF-7 cells over HeLa.